The cleft lip and palate defects in Dancer mutant mice result from gain of function of the Tbx10 gene - Bush, Jeffrey O. (National Academy of Sciences, 2004)
Cleft lip and palate (CL/P) is a common disfiguring birth defect with complex, poorly understood etiology. Mice carrying a spontaneous mutation, Dancer (Dc), exhibit CL/P in homozygotes and show significantly increased susceptibility to CL/P in heterozygotes [Deol, M. S. & Lane, P. W. (1966) J. Embryol. Exp. Morphol. 16, 543–558 and Trasler, D. G., Kemp, D. & Trasler, T. A. (1984) Teratology 29, 101–104], providing an animal model for understanding the molecular pathogenesis of CL/P. We genetically mapped Dc to within a 1-cM region near the centromere of chromosome 19. In situ hybridization analysis showed that one positional candidate gene, Tbx10, is ectopically expressed in Dc mutant embryos. Positional cloning of the Dc locus revealed an insertion of a 3.3-kb sequence containing the 5′ region of the p23 gene into the first intron of Tbx10, which causes ectopic expression of a p23-Tbx10 chimeric transcript encoding a protein product identical to a normal variant of the Tbx10 protein. Furthermore, we show that ectopic expression of Tbx10 in transgenic mice recapitulates the Dc mutant phenotype, indicating that CL/Pin Dc mutant mice results from the p23 insertion-induced ectopic Tbx10 expression. These results identify gain of function of a T-box transcription factor gene as a mechanism underlying CL/P pathogenesis.